Cross-species replication of a resistin mRNA QTL, but not QTLs for circulating levels of resistin, in human and baboon - Tejero, M.; Voruganti, V.; Proffitt, J.; Curran, J.; Göring, H.; Johnson, M.; Dyer, T.; Jowett, J.; Collier, G.; Moses, Eric; MacCluer, J.; Mahaney, M.; et al. (Nature Publishing Group, 2008)
Resistin has been associated with inflammation and risk for cardiovascular disease. We previously reported evidence of a QTL on chromosome 19p13 affecting the abundance of resistin (RETN) mRNA in the omental adipose tissue of baboons (L0D score 3.8). In this study, whole genome transcription levels were assessed in human lymphocyte samples from 1240 adults participating in the San Antonio Family Heart Study, using the Sentrix Human-6 Expression Beadchip. Lymphocytes were surveyed, as it has been proposed that their expression levels may reflect those in harder to ascertain tissues, such as adipose tissue, that are thought to be more directly relevant to disease procesn was conducted to detect loci affecting RETN mRNA levels. We obtained significant evidence for a QTL influencing the RETN expression (LOD score 10.7) on chromosome 19p. This region is orthologous/homologous to the region previously localized on baboon chromosome 19. The strongest positional candidate gene in this region is the structural gene for resistin, itself. We also found evidence for a QTL influencing resistin protein levels (LOD score 5.3) on chromosome 14q. This differs from our previously reported QTL on chromosome 18 in baboons. The different QTLs for circulating protein suggests that post-translational processing and turnover may be influenced by different or multiple genes in baboons and humans. The parallel findings of a cis-eQTL for RETN mRNA in baboon omental tissue and human lymphocytes lends support to the strategy of using lymphocyte gene expression levels as a surrogate for gene expression levels in other tissues. © 2008 Nature Publishing Group All rights reserved.